2009
DOI: 10.1353/jsm.0.0041
|View full text |Cite
|
Sign up to set email alerts
|

Checkered Flags and Mediated Friendships: Parasocial Interaction among NASCAR Fans

Abstract: Parasocial interaction (PSI) involves attraction to and subsequent relationship development with mediated characters. This study examined the nature of PSI in NASCAR fans, the fastest growing sport in the United States. Our findings indicated that PSI among NASCAR fans is a multi-dimensional concept consisting of parasocial enjoyment and parasocial attachment. Furthermore, PSI was linked to increased audience activity (involvement, intentionality and affinity), higher levels of NASCAR fandom, positive percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…On the one hand, the "sheer pleasure of being together" (Hamilton et al, 2014) characterizes the hedonic gratification that a viewer may gain from the PSI with co-viewers. Research suggests that viewers enjoy watching with others, believe interacting with other viewers is an important part of watching, and like to talk and socialize with others around them during the performance (Spinda et al, 2009). Harris (2017) found that people enjoy being with other co-viewers who are all laughing simultaneously.…”
Section: Effects Of the Para-social Interaction On The Shopping Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the "sheer pleasure of being together" (Hamilton et al, 2014) characterizes the hedonic gratification that a viewer may gain from the PSI with co-viewers. Research suggests that viewers enjoy watching with others, believe interacting with other viewers is an important part of watching, and like to talk and socialize with others around them during the performance (Spinda et al, 2009). Harris (2017) found that people enjoy being with other co-viewers who are all laughing simultaneously.…”
Section: Effects Of the Para-social Interaction On The Shopping Valuesmentioning
confidence: 99%
“…, 2014) characterizes the hedonic gratification that a viewer may gain from the PSI with co-viewers. Research suggests that viewers enjoy watching with others, believe interacting with other viewers is an important part of watching, and like to talk and socialize with others around them during the performance (Spinda et al. , 2009).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…This kind of relationship, which in some cases has led to increased fandom, has been documented in other motorsport studies of e.g. NASCAR (Spinda, Earnheardt, & Hugenberg, 2009) and Formula 1 (Hartmann, Stuke, & Daschmann, 2008). Although there is an increase in social interactions between athletes and fans it is "not yet the norm" (Boehmer 2016, p. 466).…”
Section: Literature Reviewmentioning
confidence: 73%